Thermally stimulated current spectroscopy of traps in CVD grown monolayer MoS2 - Deb, Swarup; Chakrabarti, Poulab; Chakraborti, Himadri; Das Gupta, Kantimay; Dhar, Subhabrata (Applied physics letters, 2019)
We have investigated defects in large area monolayer MoS2 films using thermally stimulated current (TSC) spectroscopy. Films are grown on c-sapphire substrates using a microcavity based chemical vapor deposition technique. A theoretical framework to analyze TSC data for a two dimensional semiconductor has been developed. The study reveals the existence of two traps with average activation energies of 670 and 850 meV. The density of these traps shows an increase followed by saturation as the sample goes through repeated thermal cycles in vacuum. Interestingly, the density returns to its initial level when the sample is exposed to the ambient condition for a sufficiently long time, suggesting that these defects are passivated by certain adsorbate groups/molecules in the ambient condition. It has been found that annealing in a sulfur environment substantially reduces the concentration of these traps. This indicates that the traps must be related to sulfur deficiency related defects.